Plan de intepretación ambiental del campus Salache. - Casnanzuela Andagua, Ana Gabriela (2023)
The present research project was carried out in the Salache campus belonging to the Technical University of Cotopaxi to create an environmental interpretation plan for the routes found on the campus, starting with a qualitative analysis of exploratory type as the first objective an evaluation of the potential interpretive index (IPI) was carried out, applying the methodology of Morales and Varela, (2006), which allowed identifying the essential characteristics that the natural and cultural resources possess, thus determining the total IPI of the Salache campus with a value of 25.5 Due to the large number of resources evaluated, it was decided to divide it into two routes. The result obtained was the route "discovering the charms of nature" with a value of 27.8, placing it on a scale of medium-high (mA), that is, with acceptable characteristics for interpretation, and the route "tourism, education and nature" with a value of 27.6, also on a scale of medium-high (mA), with acceptable characteristics for interpretation. In the second objective, the characterization of the audience was established, interviewing ten teachers from 5 academic units of the city to know the teaching method they use to improve learning concerning natural sciences and environmental education, on the other hand, the university community of the Salache campus was surveyed, in order to determine how often they visit green areas outside the city and how motivated they would be to visit it, thus defining the degree of interest of the potential audience. As a third objective, we proceeded to the design of interpretive media that would facilitate the audience's understanding of the environment: Two personal or guided interpretative media, since it consists of an interpretative script adapted for children, youth, and adults, each one consists of activities of interaction with nature since its purpose is to focus the contact between transmitter and receiver in such a way that the message is transmitted, while the theatrical script has the purpose of transmitting a message in a creative and didactic way through the use of puppets made from recyclable materials since in the design of the media the environmental care was considered discarding the use of industrial material that generates more contamination to the environment. The design means to provide an easy understanding of the resources of the place so that visitors can walk the routes and interact with the environment, contributing positively to the development of educational activities and the complementation of learning, in addition to encouraging the change of habits of consumption of plastic material and opt for reuse.